膠原病性肺高血圧症と難治性指尖潰瘍に対する当院での治療成績 - 豊田, 智子; 益田, 加奈; 木村, 耕介; 浦山, 建治; 舟木, 将雅; 藤本, 清一; 林, 喬正; 田村, 朋季; 黒田, 廣生; 森下, 佳子; 佐伯, 恭昌 (臨床リウマチ, 2009)
Pulmonary arterial hypertension (PAH) is a refractory condition associated with CTD. In addition to prostanoid, bosentan and sildenafil were approved in 2005 and 2008 respectively. Outcome has improved with these drugs. We investigated the efficacy of these drugs to refractory digital ulcer. Out of 59 SSc, 27 MCTD and 102 SLE under the treatment, 14 patients with PAH (8 SSc,4 MCTD and 2 SLE) aged from 12 to 83 (mean＝55.7) were studied. Chief complaints of these patients were breathlessness (5), digital ulcer (8), and planter ulcer (1). Bosentan was administered to all patients and sildenafil to 4 patients. IVCY was added to bosentan in pediatric SSc patient. TSS was significantly improved from 29 to 14 in pediatric SSc patient with combination of bosentan and IVCY. Bosentan seems effective not only for PAH but also for refractory digital ulcer and skin sclerosis.